2005
DOI: 10.1556/amicr.52.2005.3-4.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Potential Virulence Factors in Human Pathogenic and Saprophytic Trichoderma longibrachiatum Strains

Abstract: Potential virulence factors of 9 saprophytic and 12 clinical Trichoderma longibrachiatum strains were examined in the present study to compare their capacity to cause human infection. All of the strains were able to grow at temperatures up to 40 °C and at pH values ranging from 2.0 to 9.0. In the carbon and nitrogen source utilization experiments it was revealed that all of the strains were able to utilize a series of basic amino acids both as sole carbon and nitrogen sources. The MIC value of the antifungal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Functional studies showed HZ, its homologs (Ac-Aib-Asn-Lxx-Lxx-Aib-Pro-Lxx-Lxx-Aib-Pro-Lxxol), or mixtures containing HZ to exert embryotoxicity against Crassostrea gigas (13) as well as chlorpromazine-level neuroleptic effects in male mice (14). Crude extracts from HZ-producing fungi inhibited motility of the boar spermatozoa and quenched the mitochondrial transmembrane potential of the sperm cells at low exposure concentrations (14,15).…”
Section: Harzianin Hk VImentioning
confidence: 99%
See 1 more Smart Citation
“…Functional studies showed HZ, its homologs (Ac-Aib-Asn-Lxx-Lxx-Aib-Pro-Lxx-Lxx-Aib-Pro-Lxxol), or mixtures containing HZ to exert embryotoxicity against Crassostrea gigas (13) as well as chlorpromazine-level neuroleptic effects in male mice (14). Crude extracts from HZ-producing fungi inhibited motility of the boar spermatozoa and quenched the mitochondrial transmembrane potential of the sperm cells at low exposure concentrations (14,15).…”
Section: Harzianin Hk VImentioning
confidence: 99%
“…Furthermore, the helix-stabilizing effect of Aib in a foreign sequence even overrides the effects of helix-breaking AAs (3). Peptaibols are classified into: 1) long-sequence peptaibols (18)(19)(20) AA, typically with a centrally located Pro, and Gln residues near both termini); 2) short-sequence peptaibols (11)(12)(13)(14)(15)(16) AA, with several Aib-Pro motives, and typically either Ac-Aib-Asn-or Ac-Aib-Gln-as N-terminus); and 3) ultrashort lipopeptaibols (7 or 11 AA, with a high content in Gly and N-terminal AA acylated by a C8-C15 fatty acid).…”
Section: Introduction Peptaibolsmentioning
confidence: 99%
“…longibrachiatum and H. orientalis are the most common ones. Interestingly, no specific phylogenetic characteristics of the clinical isolates as compared to environmental isolates could be found, and no correlation between virulence or pathogenicity and genomic structure was detected (Antal et al 2005, 2006; Druzhinina et al 2008). However, most intriguingly, T. longibrachiatum not only causes disease; at the same time, it seems to be a source for potential antifungal drugs efficient against Candida and Aspergillus species (Vicente et al 2001).…”
Section: Black Sheep In the Genus Trichodermamentioning
confidence: 99%
“…The metabolites named trilongins BI-BIV and trilongin AI formed voltage-dependent, Na + /K + conductive channels in biomembranes. T. longibrachiatum is an emerging human pathogen and the main pathogen in the fungal genus Trichoderma [5,27,38]. This species is also the most common species colonizing mould troubled indoor space [9].…”
Section: Discussionmentioning
confidence: 99%
“…Crude extracts of various T. longibrachiatum isolates have been reported to contain thermostable substances that inhibited motility of boar spermatozoa and quenched the mitochondrial transmembrane potential (ΔΨ m ) of the sperm cells at low exposure concentrations [27]. In the present study, we describe the isolation, structure, toxicity and ion channel-forming activities, as well as synergistic properties, of two different sizes of peptaibols produced by T. longibrachiatum isolates originating from agricultural and clinical samples, and also from an indoor environment where serious buildingrelated symptoms of ill health were claimed.…”
Section: Introductionmentioning
confidence: 99%